Influences of a dedicated parental training program on parent–child interaction in preterm infants. Issue 3 (March 2015) - Steinhardt, Alina; Hinner, Patricia; Kühn, Thomas; Roehr, Charles C.; Rüdiger, Mario; Reichert, Jörg
Abstract Objective To investigate influences on the interaction between preterm infants and their parents by a dedicated parental training program on the care of preterm infants. Methods Standardized scenarios of mother–child interactions (50 mother–child dyads of very low birth weight infants (VLBWI), birth weight < 1500 g) were videotaped in two perinatal centers (PC-A, PC-B). The videos were reviewed and scored using a standardized instrument. In both centers, parents were integrated in the daily care by pediatric nurses, while additionally PC-A had a structured parental training program. Results PC-A and PC-B were comparable regarding patient spectrum and number of admissions of VLBWIs/year. Both centers had similar care values with respect to the "baby friendly" initiative. No significant differences were seen in characteristics of patients (gestational age, birth weight, postnatal age) and mothers (age, parity, marital status, professions). However, in scoring the mother–child interactions significant differences were observed: In contrast to PC-B the recorded behavior in mother–child dyads of PC-A was significantly more often scored as interaction-oriented. Conclusion A dedicated, structured, and actively encouraging training program for parents of preterm infants was found to be more strongly correlated toward neurodevelopmental enhancing mother–child-interactions than an approach of merely integrating parents into daily care routine.